تطبيقات الطاقة الشمسية في ضخ مياه الري والشرب لتنمية المناطق الريفية - دركوى على يصكو (Scientific Journal of University of Benghazi, 2022)
Energy is considered one of the major requirements in developing rural areas. Renewable energy sources can be used in these areas as alternative assistance to conventional energy sources such as petroleum, coal and gas which derivatives are finite in nature and increasing environmental pollution and depletion because of massive attrition. Use of solar cells to produce electrical energy and exploit it directly or store it in batteries and used it when necessary is one of the most promising methods for obtaining energy. This paper is concerned with a theoretical study for solar cell electric energy output and utilize the energy to operate a pump to raise water from wells.